EIS the scattering beamline at FERMI - Masciovecchio, Claudio (Journal of synchrotron radiation, 2015)
The Elastic and Inelastic Scattering (EIS) beamline at the free-electron laser FERMI is presented. It consists of two separate end-stations: EIS-TIMEX, dedicated to ultrafast time-resolved studies of matter under extreme and metastable conditions, and EIS-TIMER, dedicated to time-resolved spectroscopy of mesoscopic dynamics in condensed matter. The scientific objectives are discussed and the instrument layout illustrated, together with the results from first exemplifying experiments